IMPLEMENTATION OF LINEAR PROGRAM USING SIMPLEX METHOD TO OPTIMIZE PRODUCTION RESULTS IN A CONVECTION SHOP - Ananta Br Sembiring, Dwi; Jovanka, Aishikin; Wulan Lestari, Azizah; Mahyudin; Azhari Tampubolon, Rahmad (Journal of Mathematics and Scientific Computing With Applications, 2023)
This study aims to optimize production at the Belva Busana convection shop using a linear programming method with a simplex approach. This study considers production constraints such as raw material availability, working hours, and labor capacity, and focuses on maximizing profits. Data were collected through online interviews with the production team for six days, from October 27 to November 3, 2024. The linear programming model built showed optimization results with an optimal production composition of 9.6 shirts and 19.2 housedresses, resulting in a maximum profit of IDR 300,000. The results of the study prove that the simplex method is effective in allocating resources efficiently, reducing waste, and increasing productivity. This method has also proven to be practical in making production decisions to increase efficiency and profitability